THE STUDY OF MORPHOMETRIC AND DIVERSITY OF TURTLES IN AUR LAKE MUSI RAWAS REGENCY: Kajian Morfometrik dan Keanekaragaman Penyu di Danau Aur Kabupaten Musi Rawas - Widiya, Mareta; Dwi Riastuti, Reny; Febrianti, Yuli (Universitas Jambi, 2022)
One of Indonesia extinct fauna which is still found in South Sumatra but less explored is reptile. Testudinata or chelonians are examples of turtles. Aur Lake has a lot of potential issues with various species, often finding them on the shores of Aur Lake. However, those turtles do not know yet what types of species. The high intensity of catching and decreasing environmental quality can also be a threat to the existence of turtles. This research is titled